Generasi Berencana (Genre) Peduli Tumbuh Kembang : Edukasi Dasar Pijat Bayi bagi Siswa SMK - Siti Haryani; Ana Puji Astuti; Eka Adimayanti; Natalia Devi Oktarina; Riski Fizal Latif; Enggal Maharani; Linda Puspitasari (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
Infancy is a golden period of growth and development that determines a child's future quality of life. One simple form of stimulation that can support optimal growth and development is infant massage. However, knowledge and skills in infant massage among teenagers, especially vocational high school students, are still low. This community service activity aims to enhance vocational high school students' basic knowledge and skills in infant massage through the Planned Generation (GENRE) Cares About Growth and Development program. The implementation method involves interactive education, demonstrations, and hands-on practice. The results of the activity showed an increase in student knowledge of 91.14% and an increase in basic baby massage skills of 85% after the training. This program succeeded in raising awareness among teenagers about the importance of stimulating infant growth and development and equipped them with basic skills that are useful for preparing them to become smart and caring parents.   ABSTRAK Masa bayi merupakan periode emas pertumbuhan dan perkembangan yang menentukan kualitas hidup anak di masa mendatang. Salah satu stimulasi sederhana yang dapat mendukung tumbuh kembang optimal adalah pijat bayi. Namun, pengetahuan dan keterampilan pijat bayi di kalangan remaja, khususnya siswa SMK, masih rendah. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan dan keterampilan dasar pijat bayi bagi siswa SMK melalui program Generasi Berencana (GENRE) Peduli Tumbuh Kembang. Metode pelaksanaan dilakukan melalui edukasi interaktif, demonstrasi, dan praktik langsung. Hasil kegiatan menunjukkan adanya peningkatan rerata skor pengetahuan siswa sebesar 91,14 dan keterampilan dasar pijat bayi meningkat sebesar 85% setelah pelatihan. Program ini berhasil menumbuhkan kesadaran remaja tentang pentingnya stimulasi tumbuh kembang bayi serta membekali mereka dengan keterampilan dasar yang bermanfaat untuk persiapan menjadi calon orang tua yang cerdas dan peduli.